2017
DOI: 10.1017/s0007114517000940
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption pattern and risk of Barrett’s oesophagus and erosive oesophagitis: an Italian case–control study

Abstract: Knowledge about the association between alcohol and Barrett's oesophagus and reflux oesophagitis is conflicting. In this case-control study we evaluated the role of specific alcoholic beverages (red and white wine, beer and liquors) in 339 Barrett's oesophagus and 462 oesophagitis patients compared with 619 endoscopic controls with other disorders, recruited in twelve Italian endoscopic units. Data on alcohol and other individual characteristics were obtained from structured questionnaires. No clear, monotonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
(118 reference statements)
0
9
0
1
Order By: Relevance
“…In contrast to esophageal squamous cell carcinoma, alcohol consumption has not been considered associated with EAC and BE [ 52 ]. Some studies report that drinking small amounts of alcohol was a protective factor against BE, while others reported the opposite [ 15 , 53 , 54 , 55 ]. In our study, social drinking was associated with a lower risk of BE than no drinking and current drinking in both univariate and multiple logistic regression analyses.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In contrast to esophageal squamous cell carcinoma, alcohol consumption has not been considered associated with EAC and BE [ 52 ]. Some studies report that drinking small amounts of alcohol was a protective factor against BE, while others reported the opposite [ 15 , 53 , 54 , 55 ]. In our study, social drinking was associated with a lower risk of BE than no drinking and current drinking in both univariate and multiple logistic regression analyses.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 25, 2023. ; https://doi.org/10.1101/2023.03.24.23287678 doi: medRxiv preprint different from other alcoholic beverages in that moderate consumption of wine might provide a protective effect 45 , while the current MR study did not subdivide the types of alcohol consumed, which might be related to the uncorrelated results. For tea intake, epidemiological studies are likewise biased by confounding factors.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 64%
“…In respect to alcohol drinking and tea intake, most previous studies suggested that there was no association between alcohol or tea drinking and BE 10,12 , which was consistent with the results of the current MR study. However, a few studies have indicated that both wine drinking and tea intake could reduce the risk of BE 8,45 . The possible explanations for the inconsistent results of these observational and the current MR study are as follows: for alcohol drinking, on the one hand, the epidemiological studies may be biased by confounding factors, such as different lifestyles and habits between drinkers and non-drinkers.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…The concentration of ethanol may be an important factor in ethanol's biological effects. For example, liquor/spirit consumption was associated with higher risks of GERD and Barrett's esophagus, in which NOTCH was suppressed, whereas beer/wine consumption at low doses seemed to have the opposite effect [52]. Ethanol's effects on molecular pathways also depend on the context.…”
Section: Discussionmentioning
confidence: 99%